Environmental sanitation factors as prevalence support of soil transmitted helminths - Edy Sapada; Wita Asmalinda (International Journal of Public Health Science (IJPHS), 2021)
The prevalence of soil transmitted helminths (STH) is closely related to the defecation facilities for rural communities, such as: the habit of defecating openly on the ground, in gardens and using open latrines in rivers. The aim of this study was to determine the effect of environmental sanitation risk factors on the prevalence of STH infection. This study was included in an analytical epidemiological study at two locations, using a cross sectional study as the research design. The location were Sri Kembang Village, Bukit Village, which is included in Betung District, Banyuasin Regency, and South Sumatra, Indonesia for 30 days. There were 252 students as the research sample. Data analysis showed that the prevalence of T. trichiura was higher in Sri Kembang State Primary School Number 1 with mild to very severe infection degrees. The intensity of A. lumbricoides infection in Bukit State Primary School Number 1 got a higher prevalence than Sri Kembang. Open defecation, gardens or open latrines, and types of houses with dirt floors indicate environmental sanitation factors that are sufficient to support the prevalence of STH. For further research, it is recommended to examine socio-economic risk factors.